Ocular myasthenia gravis saccades as a measure of extraocular muscle function - Wong, Sui H.; Bancroft, Matthew James; Tailor, Vijay K.; Abbas, Mohamed; Sekar, Akila; Noble, Claire; Theodorou, Maria; Kaski, Diego (Frontiers in Ophthalmology, 2022)
Background: Understanding the pathophysiology of Ocular Myasthenia Gravis(OMG) is important for advancing treatment. Aim: To use modern video-oculography to characterize saccadic eye movements in OMG, including anti-AChR, anti-MuSK, anti-LRP4, and seronegative OMG. Methods: 21 OMG and 5 age-matched healthy controls underwent video-oculography (EyeLink 1000). Participants performed a sequence of horizontal saccades (3min each) at ±5°, ±10°, ±20°, followed by 3min of randomly-presented targets at ±5°±10°and ±15°. We recorded the direction, amplitude, duration, peak and average velocity of each saccade for each task for each participant. Results: Compared to controls, saccadic amplitude, duration and average velocity were smaller in OMG (p<0.021). Saccadic amplitude and velocity decreased over time, but this decrease was comparable between OMG and controls. Fixation drift and ocular disparity tended to be greater in OMG than controls. Saccadic intrusions occurred more frequently in OMG than controls (p<0.001). No significant effects of time or group by time were found on fixation drift or ocular disparity. Discussion: Saccadic velocities differed from normal controls suggesting affectation of fast-twitch fibres, although these were able to generate hypermetric ‘twitch’ or ‘quiver’ movements in the presence of even severe ophthalmoplegia. Slow-twitch muscle fibres involved in gaze holding were also affected, accounting for increased fixation drift following saccades. Our objective finding of increased fixation drift and greater number of saccadic intrusions mirror our anecdotal experience of patients with OMG who report significant diplopia despite minimal ophthalmoplegia on examination. Such microsaccades may be a surrogate for compensation of a gaze holding deficit in MG.